Open ALG Georgia's new home for open and interactive educational resources [electronic resource] (University System of Georgia, 2020)
Quoted from the homepage: With iterative texts, powerful annotation tools, rich media support, and robust community dialogue, Affordable Learning Georgia's OpenALG transforms static open textbooks into living digital works.